1995
DOI: 10.1002/jnr.490410214
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid precursor protein is modified with O‐linked N‐acetylglucosamine

Abstract: The beta-amyloid precursor protein (APP) has been implicated in the etiology of Alzheimer's disease (Kang et al.: Nature 325:733-736, 1987; Selkoe: Science 248:1058-1060, 1990; Selkoe: In Cowan et al. (eds): "Annual Review of Neuroscience." Palo Alto, CA: Annual Reviews, Inc., pp 489-519, 1994) and numerous studies have shown that beta-amyloid is involved in amyloid plaque formation (Rumble et al.: N Engl J Med 320:1446-1452, 1989; Sisodia et al.: Science 248: 492-495, 1990). Evidence is presented that APP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 44 publications
(59 reference statements)
0
91
0
Order By: Relevance
“…Although GalNAc shows a more dramatic influence on the coil (or ␣)-to-␤ structural conversion of the prion peptide, the effects associated with this sugar are probably not physiological. In contrast, the fact that O-GlcNAc glycosylation has been found in many proteins, including the tau protein and the ␤-amyloid precursor membrane protein related to the neuron degenerative Alzheimer's disease, emphasizes the physiological significance of GlcNAc (25)(26)(27)(28). O-linked GalNAc generally occurs in mucin-type glycoproteins that contain repeating units of Ser, Thr, and Pro in short regions of the peptide chain (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although GalNAc shows a more dramatic influence on the coil (or ␣)-to-␤ structural conversion of the prion peptide, the effects associated with this sugar are probably not physiological. In contrast, the fact that O-GlcNAc glycosylation has been found in many proteins, including the tau protein and the ␤-amyloid precursor membrane protein related to the neuron degenerative Alzheimer's disease, emphasizes the physiological significance of GlcNAc (25)(26)(27)(28). O-linked GalNAc generally occurs in mucin-type glycoproteins that contain repeating units of Ser, Thr, and Pro in short regions of the peptide chain (29).…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid precursor protein (APP), which forms the β-amyloid plaques characteristic of Alzheimer's disease, is both O-GlcNAc glycosylated and phosphorylated 20 . In an animal model of ALS, the O-GlcNAc levels of neurofilament protein M are decreased at the same time as its phosphorylation levels are increased 61 .…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…Neuron-specific deletion of the OGT gene in mice leads to abnormal development and locomotor defects, resulting in neonatal death 17 . The O-GlcNAc modification is abundant in the brain and present on many proteins important for transcription, neuronal signaling and synaptic plasticity, such as cAMPresponsive element binding protein (CREB) 18 , synaptic Ras GTPase-activating protein (synGAP) 19 and β-amyloid precursor protein (APP) 20 . An intriguing interplay between OGlcNAc glycosylation and phosphorylation has been observed in cerebellar neurons, wherein activation of certain kinase pathways reduces O-GlcNAc levels on cytoskeleton-…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that increased flux into the glucosamine pathway could quantitatively or qualitatively alter the O-linked glycosylation state of various proteins involved in insulin action and thereby affect their function via numerous potential mechanisms (Hawkins et al, 1999). In addition, O-linked glycosylation of serine or threonine residues can competitively inhibit phosphorylation at the same sites (Griffith et al, 1995a;Hart et al, 1996). The reciprocal glycosylation/phosphorylation state of key serine/threonine kinase could affect the tyrosine phosphorylation state and thus the activation of insulin receptor substrate-1 or other upstream signaling molecules Hawkins et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of a link between analogous O-GlcNAc modification and diabetes. It has been known that many cytoskeletal proteins like microtubule-associated proteins, neurofilaments and synapsin are multiple O-GlcNAc (Griffith et al, 1995a(Griffith et al, , 1995bArnold et al, 1996;Cole and Hart, 1999), and defects in O-GlcNAc metabolism are associated with human disease such as neurodegeneration, diabetes mellitus, and cancer (Griffith et al, 1995b;Yao and Coleman, 1998;Hanover, 2001;RexMathen et al, 2001;Liu et al, 2009). The positive cell of O-GlcNAc was highly (40-50%) increased in the glomeruli and tubuli in the kidney of diabetic patient (Degrell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%